Lama Penggunaan Gadget Sebagai Pemicu Peningkatan Derajat Miopia - Tulangow, Dwintya Saffira; Lastriyanti, Lastriyanti; Sapeni, Muhammad Al-Amin R. (FORIKES, 2025)
Myopia is a condition of blurred distance vision, and there is a tendency to squint to see something. One of the causes of myopia is the use of gadgets for a long time. The behavior of using gadgets for a long time can cause eye fatigue, stress on the eye accommodation muscles and will make myopia continue to develop. Thus, it is necessary to conduct research that aimed to determine the relationship between the duration of gadget use and the degree of myopia in students. This study applied a cross-sectional design. Data collection was carried out directly by filling out a questionnaire about the identity of the respondents, the intensity of gadget use, and the degree of myopia. Data were analyzed using the Chi-square test. The results showed that there was a difference in the proportion of severe myopia between students with and without long-term gadget use, which was indicated by a p value = 0.001, so it was interpreted that there was a significant relationship between the duration of gadget use and the degree of myopia. Thus it could be concluded that the duration of gadget use is a trigger for increasing the degree of myopia in students.Keywords: myopia; gadget; degree of myopia; students ABSTRAK Miopia adalah keadaan pengelihatan jauh yang kabur, dan terdapat kecenderungan memicingkan mata untuk melihat sesuatu. Salah satu penyebab miopia adalah pengggunaan gadget yang lama. Perilaku penggunaan gadget dalam waktu lama dapat menyebabkan mata lelah, stress pada otot akomodasi mata dan akan membuat miopia terus berkembang. Dengan demikian, perlu dilakukan penelitian yang bertujuan untuk untuk mengetahui hubungan antara lama penggunaan gadget dengan derajat miopia pada mahasiswa. Penelitian ini menerapkan rancangan cross-sectional. Pengumpulan data dilakukan secara langsung melalui pengisian kuesioner tentang identitas responden, intensitas penggunaan gadget, dan derajat miopia. Data dianalisis menggunakan uji Chi-square. Hasil penelitian menunjukkan bahwa terdapat perbedaan proporsi derajat miopia berat antara mahasiswa dengan penggunaan gadget lama dan tidak, yang ditunjukkan dengan nilai p = 0,001, sehingga diinterpretasikan bahwa ada hubungan yang signifikan antara lama penggunaan gadget dengan derajat miopia. Dengan demikian bisa disimpulkan bahwa lama penggunaan gadget merupakan pemicu peningkatan derajat miopia pada mahasiswa.Kata kunci: miopia; gadget; derajat miopia; mahasiswa